Biomechanics of tooth movement: Biomekanika pergerakan gigi - Ardiansyah S. Pawinru; Serliawati (Makassar Dental Journal PDGI Makassar, 2021)
Introduction: Orthodontic treatment results in a tooth movement that aims to correct the abnormal tooth position into a normal and aesthetic position. The principle of tooth movement that applies pressure produces remodeling which can be seen from a microscopic. Objective: The objective of this article is aimed to describe the biomechanics of tooth movement that occurs when using removable orthodontics. Methods: scientific evidence are taken from literature to support the clear and detailed informa-tion. Conclusion: Orthodontic tooth movement is based on biological principles. The intermittent or continuous forces applied to the teeth, altering the mechanical system and then limiting the cellular response leading to bone adaptation in a new functional environment.